The Role of Social Work in Facing the Negative Effects of Cyberbullying on Adolescents in Saudi Arabia - Al-Sulami, Meaad Shahad Zayed (Journal of Humanities & Social Sciences, 2023)
This research aims to explore the negative effects of cyberbullying on adolescents in Saudi Arabia and assess the role of social work in addressing the issue. The first objective of this study is to identify the negative effects of cyberbullying on adolescents in Saudi Arabia. The second objective of this study is to assess the role of social work in addressing the issue of cyberbullying in Saudi Arabia. The third objective of this study is to identify the challenges that social workers face in addressing the issue of cyberbullying. This research work is qualitative in nature and follows the systematic review approach to interpret the outcomes. The study employed a qualitative secondary approach, utilizing existing literature and data to identify the key issues related to cyberbullying and the challenges faced by social workers in addressing the issue. The research findings indicate that cyberbullying has serious negative effects on adolescents, including emotional distress, decreased self-esteem, and negative impacts on their academic performance. The role of social work in addressing cyberbullying is crucial, as social workers have the skills and training to provide support for victims. However, the study highlights the challenges faced by social workers, including a lack of training and resources, as well as legal and cultural barriers that make it difficult to effectively address the issue. Based on these findings, the study concludes that a comprehensive and collaborative response is required from a variety of stakeholders, including social workers, policymakers, educators, and technology companies, to effectively address the issue of cyberbullying and protect the well-being of young people in Saudi Arabia. The study reached a number of recommendations, the most important of which are: Social work education and training, Awareness and education, improved support systems, and Policy development.